2015
DOI: 10.1371/journal.pone.0133076
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Lymph Node Involvement in Large Scale Operable Node-Positive Esophageal Squamous Cell Carcinoma Patients: A 10-Year Experience

Abstract: BackgroundLymph node (LN)-related factors including the number of LN regions involved, the LN ratio (LNR), and the number of metastatic LNs are strong prognostic indicators for esophageal squamous cell carcinoma (ESCC) patients. Accurately staging LN involvement may improve the stratification of patients and guide the management of patients.MethodsA total of 688 potentially resectable patients who had regional LN metastases were enrolled in this retrospective study.ResultsESCC involving a single region was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Since it is well known that metastasis to lymph nodes is associated with a poorer prognosis in patients with ESCC, a biomarker that could predict metastatic potential in individual cases of ESCC would be clinically useful. There are several reports of candidate markers, such as trypsin, the γ 2 chain of laminin‐5, RCAS1 and p21 (WAF1), which have been shown to be correlated with lymph node metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Since it is well known that metastasis to lymph nodes is associated with a poorer prognosis in patients with ESCC, a biomarker that could predict metastatic potential in individual cases of ESCC would be clinically useful. There are several reports of candidate markers, such as trypsin, the γ 2 chain of laminin‐5, RCAS1 and p21 (WAF1), which have been shown to be correlated with lymph node metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Cases of esophageal cancer in China are typically ESCC, which is the fifth most common type of cancer in China and has an associated mortality rate ranked as the fourth highest among malignant types of cancer (3). ESCC may be spread in vivo via the direct invasion of surrounding tissues, including lymphatic metastasis, hematogenous metastasis and implantation metastasis (2).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that ESCC primarily exhibits metastasis via lymphatic vessels in the early stages (1,2). Therefore, investigating the factors that may affect lymph angiogenesis in ESCC, as well as the molecular mechanisms underlying lymphatic metastasis, may have vital clinical significance towards the diagnosis and treatment of ESCC (3). Vascular endothelial growth factor C (VEGF-C) is a member of the vascular endothelial growth factor family, and previous studies have demonstrated that VEGF-C participates in the lymph angiogenesis of a variety of malignant tumors, resulting in the lymph node metastasis of tumors and thus affecting prognosis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node metastasis (LNM), or positive lymph nodes (PLN) usually occurs early in the development of ESCC, which have a prominent impact on the evaluation of tumor stage and the prognosis of patients (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%